Christianity in the second century: themes and developments - Paget, James Carleton; Lieu, Judith (Cambridge University Press, 2017)
"Christianity in the Second Century shows how academic study on this critical period of Christian development has undergone substantial change over the last thirty years. The second century is often considered to be a time during which the Christian church moved relentlessly towards forms of institutionalisation and consolidated itself against so-called heretics"--
Includes bibliographical references (pages 309-348) and index
"This volume is the result of a conference, entitled 'The Christian Second Century', which was held between March 14th and 16th, 2013, at the Centre for Research in the Arts, Social Sciences and Humanities (CRASSH), University of Cambridge."
Keywords: Konferenzschrift -- 2013 -- Cambridge; Geschichte 100-200; Frühchristentum